Successful Treatment of Carcinomatous Central Airway Obstruction with Bronchoscopic Electrocautery Using Hot Biopsy Forceps during Mechanical Ventilation - Ugajin, Motoi (Case Rep Oncol Med, 2017)
We report the case of a 72-year-old man with occlusion of the left main bronchus due to squamous cell carcinoma of the lung. He required tracheal intubation and mechanical ventilation because of the aggravation of atelectasis and obstructive pneumonia. Electrocautery using hot biopsy forceps was performed during mechanical ventilation with a 40% fraction of inspired oxygen. He was extubated following improvement in the atelectasis and obstructive pneumonia and discharged with shrinkage of the tumor after chemotherapy. We describe a safe electrocautery procedure using hot biopsy forceps during mechanical ventilation with reference to previous reports.